Corporate social responsibility and sporting events. A systematic review of scientific production - Fonseca, Ingrid; Bernate, Jayson; Tuay, Diego (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The impact of sporting events is related to social, economic, environmental and political aspects that affect the development of communities through social integration. The aim of the study was to examine the current state of research on sporting events and corporate social responsibility. The research design is a systematic review of the scientific literature (SLR) of 268 documents in the Scopus, SportDiscus, Proquest and Dialnet databases. After the filtering process, 26 articles were selected that met the inclusion criteria. According to this review, it is concluded that in sporting events it is necessary to have the interest groups from the moment of planning the event, generate initiatives to avoid environmental damage in the construction of stages, seek economic sustainability, and give conscious use to the sports infrastructure built and leave a long-term positive legacy.